2017
DOI: 10.1177/1558944717702471
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Hand and Wrist Photogoniometry

Abstract: At present, photogoniometry is not an acceptable alternative to manual goniometry for determining wrist and digit range of motion in general. Joint-specific photogoniometry should be the subject of future study, as should relevant imaging and software technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…40 In manual photographic measurement, Georgeu et al compared lateral image measurement of the ring or little fingers with standard goniometry in 20 patients. 41 In their study, the average difference was 1°(SD: 6°, 95% Cl: 0°to + 2°), and the 95% LOA was −11°to + 13°, which was beyond the 42 We found our results comparable to these measurements. In our study, even if we set a ± 5°as the level of clinical acceptance, 40.6% of parameters had strictly reached the clinical agreement, and another 18.8% of parameters had almost achieved the agreement.…”
Section: Discussionsupporting
confidence: 71%
“…40 In manual photographic measurement, Georgeu et al compared lateral image measurement of the ring or little fingers with standard goniometry in 20 patients. 41 In their study, the average difference was 1°(SD: 6°, 95% Cl: 0°to + 2°), and the 95% LOA was −11°to + 13°, which was beyond the 42 We found our results comparable to these measurements. In our study, even if we set a ± 5°as the level of clinical acceptance, 40.6% of parameters had strictly reached the clinical agreement, and another 18.8% of parameters had almost achieved the agreement.…”
Section: Discussionsupporting
confidence: 71%
“…82 For finger ROM, three studies in adults demonstrated that smartphone photography had excellent interand intra-rater reliability for MCP, PIP and DIP joint flexion and extension measurements. [83][84][85] However, only two of the three studies demonstrated high validity when compared to manual goniometry. In addition, there were no statistical differences between photo measurements of the wrist and fingers taken by patients' family members when compared to those obtained by specialist physicians.…”
Section: Rom Assessmentmentioning
confidence: 96%
“…A technique that overcomes this hindrance is photogoniometry, which has shown acceptable agreement levels both with goniometry and when tested for interobserver and intraobserver measurements. 6,7 Although photogoniometry decreases the amount of equipment required, making at-home measurement possible, static images cannot provide a full ROM evaluation. As the hand comprises numerous small joints, another potential obstacle to manual hand goniometry is the length of the process, which can take as long as 30 minutes.…”
Section: Introductionmentioning
confidence: 99%